Predation performance of Podisus nigrispinus (DALLAS) (Hemiptera: Pentatomidae) in caterpillars of Spodoptera eridania (CRAMER) (Lepidoptera: Noctuidae) - de Carvalho, José Romário; Araujo Junior, Luis Moreira; Damascena, Alixelhe Pacheco; Passos Ikuno, Pedro Hiroshi [UNESP]; de Oliveira, Regiane Cristina [UNESP]; Zanuncio Junior, José Salazar; Pratissoli, Dirceu; Zanuncio, José Cola (Elsevier, 2025)
Reducing the diversification of agroecosystems has minimized the occurrence of natural enemies and favored that of pest insects. Spodoptera eridania (CRAMER) (Lepidoptera: Noctuidae) is a cosmopolitan insect-pest that has a high range of economically important crops as hosts. In order to suppress the population increase of this pest, biological control becomes an interesting alternative. The objective of this study was to verify the predatory performance of Podisus nigrispinus (DALLAS) (Hemiptera: Pentatomidae) on S. eridania caterpillars as a function of predator age, aiming to understand their potential for your use as a biological control agent in pest management programs. The performance bioassay was carried out using the methodology of functional response with measures repeated in the time, seeking to understand the influence of the age of the predator and the density of prey on its potential. The sphericity between the ages and predation of the predator was verified. A survival analysis was performed to verify if the number of preys would affect the predator's longevity. The functional response of type II was observed, with the Holling model better fitted to the data. The parameters, search efficiency (a) and handling time (Th), were affected by the age of the predator. The efficiency tended to decrease, while the handling time increased, as the predator's age increased. However, P. nigrispinus was estimated to consume 145 caterpillars up to the age of 17 days. Younger predators have the greatest estimation of the maximum number of S. eridania caterpillars consumed. The predator's survival curves according to number of preys were similar. Moreover, the predation habit occurs throughout the adult age of the predator.
Keywords: Age of insect; Biological control; Functional response; Integrated pest management